Multiple viral infections and antimicrobial use in hospitalized children with respiratory illness during pandemic and early post-pandemic era, Taiwan - Chyi-Liang Chen; Yi-Ching Chen; Hsuan-Ling Hsiao; Yi-Jung Chang; Hsin-Chieh Li; Merve Arslan Aydin; Cheng-Hsun Chiu (Heliyon)
Background: Respiratory viral infections significantly burden pediatric populations. These infections are especially concerning in hospitalized children. Co-infection with bacteria may contribute to severe disease in children with respiratory viral infections. Methods: The trend of children's respiratory infections during and after the pandemic was analyzed. FilmArray RP was used for etiology surveys of hospitalized children with acute respiratory illness in a medical center in northern Taiwan from October 2022 to March 2023. Antimicrobial days of therapy (DOT) were used to measure and compare the antimicrobial consumption between FilmArray RP test-positive and -negative groups. We also reviewed Taiwan CDC's surveillance data in the study period. Results: Among 418 children tested, 271 cases showed positive results; 48.8 % (204/418) had a single virus identified. Multiple viruses were co-circulating in the community starting in September 2022. An increase in the number of influenza cases with severe complications in Taiwan was observed after October 2022. Following these viral infections, cases of invasive pneumococcal disease (IPD) began to increase from September 2022 onward. The FilmArray RP test results did not influence physicians' antibiotic prescribing, as there was no difference in DOT between the test-positive (single, double, or triple viruses-positive) and test-negative groups. However, the average DOTs in both groups were less than 10. Conclusions: Multiple viruses were co-circulating in the community after the pandemic likely due to immune debt. Pediatric physicians continued to use antibiotics for febrile symptoms in hospitalized children with respiratory illness, even when viral pathogens were identified.